The Oxford handbook of theology, sexuality, and gender - Thatcher, Adrian (Oxford, United Kingdom Oxford University Press, 2015)
The Oxford handbook of theology, sexuality, and gender presents an unrivaled overview of the theological study of sexuality and gender. Not merely contentious and pervasive topics, sexuality and gender have escalated in importance within theology. Theologians increasingly agree that even the very doctrine of God cannot be contemplated without a prior grappling with each. Featuring 41 newly-commissioned essays, written by the foremost scholars in the discipline, this authoritative collection presents and develops the latest thinking in the area. Divided into eight thematic sections, the Handbook explores key methodological approaches, concepts, and issues, as well as current controversies within various denominations. Selected essays draw on reason as a distinct source of theology, discussing evolutionary biology and behavioural genetics, psychology, anthropological research, philosophical research, and queer theory. It examines the history of theologies of sexuality and gender, with close analysis of the Bible and the Christian tradition. The final section considers theology in relation to different expressions of sexual identities. This volume is an essential reference for students and scholars, which will also stimulate further research.
part 1. Methods. Introduction / Adrian Thatcher ; The theological study of sexuality / Elizabeth Stuart ; The theological study of gender / Tina Beattie ; Doctrine And sexuality / Eugene F. Rogers Jr. -- part 2. What theologians need to know. Contributions from biology / Neil Messer ; Contributions from psychology / Brendan Callaghan SJ ; Contributions from anthropology / Anna Stewart and Simon Coleman ; Contributions from sociology / Marta Trzebiatowska ; Contributions from philosophy / Cynthia R. Nielsen and Michael Barnes Norton ; Contributions from queer theory / Patrick S. Cheng -- part 3. Sexuality and gender in the biblical world. Marriage and sexual relations in the world of the Hebrew Bible / Ken Stone ; Marriage and sexual relations in the New Testament world / William Loader ; Same-sex relations in the biblical world / Theodore W. Jennings Jr. ; The construction of gender in the New Testament / Colleen M. Conway -- part 4. Sexuality and gender in Christian tradition. Desire and the body in the patristic period / Mathew Kuefler ; Duns Scotus on the female gender / Marilyn McCord Adams ; Reproducing medieval Christianity / Ruth Mazo Karras ; Chaste bodies, salacious thoughts: the sexual trials of the medieval clergy / Dyan Elliott ; Sex and marriage in the Protestant tradition, 1500-1900 / John Witte Jr. -- part 5. Controversies within the churches. Conflicts within the Roman Catholic Church / Linda Hogan ; Conflicts within the Anglican Communion / Jane Shaw ; Pentecostal churches and homosexuality / William K. Kay and Stephen J. Hunt ; Theology and practice in evangelical churches / Andrew Goddard ; Conflicts within the Black churches / Angelique Harris -- part 6. Inter-religious conversations. Judaism / Ronit Irshai ; Islam / Asma Barlas ; Hinduism / Mandakranta Bose ; Buddhism / Rita M. Gross -- part 7. Concepts and issues. Violence and justice / Pamela Cooper-White ; Sexual pleasure / Margaret D. Kamitsuka ; Desire and love / Ola Sigurdson ; HIV/AIDs / Mary Jo Iozzio -- part 8. Sexual theologies for all people. People beginning sexual experience / Michael G. Lawler and Todd A. Salzman ; Wives and husbands / Thomas Knieps-Port le Roi ; Families / Adrian Thatcher ; Gay affections / Gerard Loughlin ; Lesbians / Lisa Isherwood ; Bisexual people / Margaret Robinson ; Intersex and transgender people / Susannah Cornwall ; Disabled people / Deborah Beth Creamer ; Friends and friendship / Steve Summers.
Includes bibliographical references and index.
Keywords: Sex -- Religious aspects; Sex role -- Religious aspects; Theology